2012
DOI: 10.1128/aac.05663-11
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Plant-Derived Antifungal Acetylenic Acid Mediates Its Activity by Interfering with Fatty Acid Homeostasis

Abstract: c 6-Nonadecynoic acid (6-NDA), a plant-derived acetylenic acid, exhibits strong inhibitory activity against the human fungal pathogens Candida albicans, Aspergillus fumigatus, and Trichophyton mentagrophytes. In the present study, transcriptional profiling coupled with mutant and biochemical analyses were conducted using the model yeast Saccharomyces cerevisiae to investigate its mechanism of action. 6-NDA elicited a transcriptome response indicative of fatty acid stress, altering the expression of genes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
(70 reference statements)
0
11
1
Order By: Relevance
“…Moreover, metronidazole showed a potentiation of its antifungal effect when combined with plant extracts [122,123], as did fluconazole with other phytocomponents [114]. Using genetic and biochemical approaches, Xu et al showed the antifungal activity of a plant-derived acetylenic acid by interfering with the fatty acid homeostasis pathway [124].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Moreover, metronidazole showed a potentiation of its antifungal effect when combined with plant extracts [122,123], as did fluconazole with other phytocomponents [114]. Using genetic and biochemical approaches, Xu et al showed the antifungal activity of a plant-derived acetylenic acid by interfering with the fatty acid homeostasis pathway [124].…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Acetylenic fatty acids have been widely studied by medicinal chemists due to their interesting antimicrobial properties such as antifungal (Carballeira, 2008; Carballeira et al, 2006; Carballeira et al, 2005; Gershon and Shanks, 1978; Li et al, 2003; Li et al, 2008; Xu et al, 2012), antiprotozoal (Carballeira et al, 2012; Tasdemir et al, 2010), and antibacterial activities (Konthikamee et al, 1982; Morbidoni et al, 2006). Acetylenic fatty acids are mainly produced by certain plants as a chemical defense against microorganisms (Cahoon et al, 2003; Carballeira, 2008; Fatope et al, 2000; Li et al, 2003; Li et al, 2008; Xu et al, 2012). Among the acetylenic fatty acids, the 2-hexadecynoic acid (2-HDA) has received the most attention for its antimicrobial and cytotoxic properties (Carballeira et al, 2012; Carballeira et al, 2006; Gershon and Shanks, 1978; Morbidoni et al, 2006; Upreti et al, 1981; Wood and Lee, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The power of the protocol is that all nine parameters are obtained from a single z-stack of CLSM scans of an individual biofilm preparation rather than from separate preparations in separate experiments. We first assessed the effectiveness of this protocol on five crude extracts and extract-derived compounds previously demonstrated to inhibit the growth of C. albicans in suspension or on a plastic surface (54)(55)(56)(57)(58)(59)(60)(61)(62). All five extracts and all five extract-derived antifungal agents caused aberrant biofilm formation, on the basis of a comparison with the phenotypic profiles afforded by the nine parameters of the untreated control preparations, but the profiles differed between extracts in some cases and between the extract and the extractderived agent in two cases.…”
mentioning
confidence: 99%